The Effect of Sound Therapy in Increasing Calmness and Reducing Stress on Working Muslim Women in Malaysia - Dini Farhana Baharudin; Melati Sumari (Elsevier Ltd, 2024)
The aim of this study was to evaluate the efficacy of sound therapy in increasing calmness and reducing stress on working Muslim women in Malaysia. The design of this study was experimental using single group pretest-posttest. Eighty-eight Muslim women who are married and employed, participated in this study and their level of calmness and stress were measured before and after they were given two types of sound therapy intervention, the first being sounds of nature and the second, a recitation of Quranic verse. Both types of sound therapy shows significant increase in participants' calmness and reduction of their stress level but the second type of sound therapy (i.e. recitation of Quranic verse) shows better results than the first type (sounds of nature). These findings demonstrate that an intervention using sound therapy produces positive effects on the body. The result suggests that the use of sound therapy for working Muslim women in Malaysia may improve their calmness and reduce their stress level thus, underscore the need for additional research.